Clinical Features and Risk Factors of Mortality in Patients with Posterior Reversible Encephalopathy Syndrome - Hong-Wei Cui; Ru-Yi Lei; Bo-Ai Zhang (Behavioural Neurology)
Objective. Although the prognosis of posterior reversible encephalopathy syndrome (PRES) is usually favourable and most patients wholly recover, the disorder can result in death in some patients. To date, the data on clinical features and risk factors for death are still lacking; therefore, we aim to investigate the clinical features and long-term prognostic risk factors of PRES in the present study. Methods. The patients with PRES were identified from the First Affiliated Hospital of Zhengzhou University from June 2011 to June 2020. Clinical characteristics, laboratory tests, magnetic resonance imaging examinations, and treatment of all patients were analyzed retrospectively. All patients were followed up by telephone. Finally, the patients were divided into the survival group and death group for prognosis analysis. Results. A total of 92 patients with PRES were included; 84.8% of whom were female, with an average age of 25.4 (5–66) years at the onset of PRES. Epilepsy was the main clinical manifestation (72.8%). The in-hospital mortality rate was 2.17%. The 3-year all-cause survival rate for PRES patients was 86%. In univariate analysis, patients with systemic lupus erythematosus (P=0.027) and blood transfusion history within 1 month before onset (P=0.027), need for dialysis (P≤0.001), nephritis (P=0.010), stroke (P=0.016), and heart failure (P=0.016) were associated with death. In multivariate analysis, we found that heart failure (OR=0.095, 95% CI 0.020 to 0.441) and stroke (OR=0.033, 95% CI 0.002 to 0.467) were independent risk factors for death in PRES patients, while pregnancy was a protective factor for death in PRES patients (OR=7.978, 95% CI 1.446 to 44.006). Conclusions. Our results indicate that PRES could be considered as a sign of a very high-risk patient. We also demonstrated that heart failure and stroke were independent risk factors for death in patients with PRES; moreover, pregnancy was a protective factor.